The Cytotoxic Effects of Glycyrrhiza glabra L. Root Extract on 4T1 Cell Line Derived from BALB/c Mice Mammary Tumors - A Hamta; SMA Shariatzadeh; M Soleimani Mehranjani; H Fallah Huseini; F Hosseinabadi (Institue of Medicinal Plants, ACECR, 2014)
Background: Glycyrrhiza glabra L. (G. glabra) root has been used in traditional medicine for treatment of several diseases. The main active constituent of G. glabra is glycyrrhizic acid with antioxidant property. The cytotoxic effects of several compound isolated from different plants have been attributed to their antioxidant properties. Objective: The present work was aimed to investigate the in-vitro cytotoxic screening of G. glabra root extract against 4T1 cell line derived from BALB/c mice mammary tumors. Methods: 4T1 cells were cultured in RPMI-1640 medium with 10% FBS and penicillin/streptomycin. Then cells treated with different concentration of G. glabra extract (50, 100, 200, 400, 800 µg/ml), taxol (1.25, 2.5, 5, 10, 20 nM) alone and in combination G. glabra and taxol for 24, 48, 72 hrs. Viability of the cells was measured through trypanblue and MTT staining. The cells morphology was studied using fluorescent dye. Results: G. glabra root extract and taxol showed significant cytotoxic effects on breast cancer cells. Condensation and deformation of the nuclei were also observed similarly for both treatments. Moreover in combination therapy, G. glabra extract enhances taxol induced cytotoxicity in cancerous cells. Conclusion: G. glabra root extract and taxol showed cytotoxicity effects and morphological changes in 4T1 cells. This reduction in the viability of the cells was dependent on dose and time.